2022
DOI: 10.3390/ijms23158326
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Lipidome Fingerprint: New Assistance to Characterize Platelet Dysfunction in Obesity

Abstract: Obesity is associated with a pro-inflammatory and pro-thrombotic state that supports atherosclerosis progression and platelet hyper-reactivity. During the last decade, the platelet lipidome has been considered a treasure trove, as it is a source of biomarkers for preventing and treating different pathologies. The goal of the present study was to determine the lipid profile of platelets from non-diabetic, severely obese patients compared with their age- and sex-matched lean controls. Lipids from washed platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Lipid species of basal platelets reported here were quite similar to the pattern described by Leidl et al 27 as well as by Valkonen et al 13 and align reasonably with those reported by Han et al 9 . Similar species profiles were also reported recently for platelets isolated from healthy subjects and obese patients 29 . However, we could not confirm the presence of short chain PC 18:0, 20:0, 24:0, which were found upregulated in platelets of acute www.nature.com/scientificreports/ coronary syndrome patients 30 .…”
Section: Basal Lipid Class Concentrations and Species Profilessupporting
confidence: 89%
“…Lipid species of basal platelets reported here were quite similar to the pattern described by Leidl et al 27 as well as by Valkonen et al 13 and align reasonably with those reported by Han et al 9 . Similar species profiles were also reported recently for platelets isolated from healthy subjects and obese patients 29 . However, we could not confirm the presence of short chain PC 18:0, 20:0, 24:0, which were found upregulated in platelets of acute www.nature.com/scientificreports/ coronary syndrome patients 30 .…”
Section: Basal Lipid Class Concentrations and Species Profilessupporting
confidence: 89%
“…Previous studies have confirmed platelet hyperreactivity as a vital pathological factor contributing to high thrombotic risk in metabolic disorders such as obesity, diabetes, hypertension, and hyperlipidemia. 62–65 Notably, GUDCA, an endogenous bile acid species, exhibited significantly lower plasma levels in patients with hyperglycemia. 20 Our previous study, along with other publications, had also verified that GUDCA maintained metabolic homeostasis and ameliorated metabolic disorders including atherosclerosis, diabetes, and fatty liver disease.…”
Section: Discussionmentioning
confidence: 98%
“…Single-cell technologies have opened a unique window into understanding intraindividual heterogeneity among hematopoietic stem cells [ 17 ] and megakaryocytes [ 18 , 19 ]. Transcriptomics [ 20 ], proteomics [ 21 ], and novel lipidomics [ 22 ] have enabled multiple pathways to be examined simultaneously in large and varied cohorts of individuals.…”
Section: Historical and Contemporary Perspectives And Technologiesmentioning
confidence: 99%
“…Studies of the platelet proteome and phosphoproteome in obese individuals and matched controls have identified differentially activated signaling pathways that translate into altered in vitro aggregation phenotypes [ 80 , 81 ]. More recently, comprehensive study of platelet lipids—the “lipidome” —has revealed differences between obese and nonobese individuals [ 22 ].…”
Section: Platelet Heterogeneity At the Individual Level: Inherited Ac...mentioning
confidence: 99%